1998
DOI: 10.1002/(sici)1097-0134(19981001)33:1<74::aid-prot7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Screening a peptidyl database for potential ligands to proteins with side-chain flexibility

Abstract: The three key challenges addressed in our development of SPECITOPE, a tool for screening large structural databases for potential ligands to a protein, are to eliminate infeasible candidates early in the search, incorporate ligand and protein side-chain flexibility upon docking, and provide an appropriate rank for potential new ligands. The protein ligand-binding site is modeled by a shell of surface atoms and by hydrogen-bonding template points for the ligand to match, conferring specificity to the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 61 publications
0
82
0
1
Order By: Relevance
“…In some methods, the ligand's pose is optimized before varying the protein side-chains [49], while in more recent methods, both the ligand and side-chain conformations are explored simultaneously [50], [51]. The latter methods have demonstrated significant improvement over rigid-protein docking [52], [53].…”
Section: B Selective Dockingmentioning
confidence: 99%
“…In some methods, the ligand's pose is optimized before varying the protein side-chains [49], while in more recent methods, both the ligand and side-chain conformations are explored simultaneously [50], [51]. The latter methods have demonstrated significant improvement over rigid-protein docking [52], [53].…”
Section: B Selective Dockingmentioning
confidence: 99%
“…It was shown that the methods described in that protocol are very useful in predicting correct poses of bound ligands by accounting for induced fit effecting such as small movements in the backbone and significant changes in side-chain conformations of protein residues. Other groups have also developed protocols for accounting for protein flexibility in docking [10][11][12][13][14]. However, modeling large-scale changes in backbone conformations of proteins, including large loop movements, present significant challenges and therefore may require alternative methods.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Nevertheless, molecular docking has some practical advantages. Although it has only a modest ability to distinguish between two compounds that both fit in an active site, it can reliably screen out compounds that do not fit in a binding site or that have grossly wrong electrostatic properties.…”
Section: Introductionmentioning
confidence: 99%